Performance Accountability Financial Reports of Saving and Loan Cooperatives in East Lombok (Study on KSUSPPS Bina Al-Mandiri Syaria'ah) - Salmato; Baiq Anggun Hilendri Lestari; Lalu Takdir Jumaidi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study analyzes the accountability of financial reporting performance in one of the cooperatives in East Lombok Regency, the KSUSPPS Bina Al-Mandiri Syari'ah Cooperative. This study aims to determine the extent to which the performance accountability of the KSUSPPS Bina Al-Mandiri Syari'ah Cooperative's financial reports is accountable to members and the public. This study uses a descriptive-qualitative approach, collecting data through observation, interviews, and documentation. The results showed that the KSUSPPS Bina Al-Mandiri Syari'ah Cooperative needed to be more fully accountable and transparent in managing the cooperative. KSUSPPS Bina Al-Mandiri Syari'ah Cooperative, in compiling financial reports, has included proof of transactions but has not integrated them; disclosures are made only in the form of financial report items, and financial reports are available for each unit containing a statement of financial position and profit and loss statement. Documents for cooperative activities are available in full and can be accessed by the community and members.